Accuracy of the Babolat Pop sensor for assessment of tennis strokes in structured and match play settings - Raymond, C. J.; Madar, T. J.; Montoye, A. H. K. (Journal of Sport and Human Performance, 2019)
The Babolat Pop sensor (POP) detects tennis stroke types (forehand, backhand, overhead, serve, volley) and spins (topspin, flat, slice), but it has not yet been validated for use. Therefore, this study`s purpose was to validate the POP in structured and match play settings. Seventeen collegiate tennis players (9 women, 8 men) wore the POP on their dominant wrist while participating in 2 sessions. Session 1 (structured) consisted of 10 drills of 5-10 shots each, each focusing on a specific shot type (forehands, backhands, serves, overheads, volleys) and spin (topspin, flat, slice). In session 2 (match play), participants played 6 games against an opponent. For both sessions, researchers observed and recorded the number and type of shot and spin hit for comparison to those recorded by the POP. Mean absolute percent error (MAPE) and bias were calculated to assess accuracy, with sub-analyes by sex and player ranking. The POP underestimated most shots and spins during the structured session, with MAPE averaging 32.0% and ranging 5.3-93.5%. MAPE was 9.4% overall but ranged 11.3-223.9% in the match play setting. MAPE and bias were significantly lower for males than females for most shots in the structured setting but only 2 shot/spin types in the match play setting. Player ranking did not affect sensor accuracy. In conclusion, the POP had lowest error for detecting major stroke types, with similar or better accuracy during match play than in structured drills.